Rainwater Pressure Electic Generator Model Using Piezoelectric - Susanti, Ai; Sari, Della Puspita; Nauzy, Muhammad Azar; Widaningsih, Sri; Hamdiyanti, Yanti; Novianingsih, Khusnul (Universitas Pendidikan Indonesia (UPI), 2021)
Renewable energy technology is needed to deal with climate change and reduce non-renewable energy such as oil and coils, which are still widely used until now. In this research, we design a rainwater pressure electric generator model using a piezoelectric. We use the pressure from water falling of drainage, and then turn it into electrical energy with a piezoelectric sensor. The sensor will generate an electric voltage that will be saved it into batteries. The results show the high pressure of waterfall will produce high electrical energy, and it depends on the volume and height of the falling water.